Thirty years of connectivity conservation planning: an assessment of factors influencing plan implementation. (30th September 2019) - Keeley, Annika T H; Beier, Paul; Creech, Tyler; Jones, Kristal; Jongman, Rob HG; Stonecipher, Grace; Tabor, Gary M
Abstract: Connectivity conservation is an emergent approach to counteracting landscape fragmentation and enhancing resilience to climate change at local, national, and global scales. While policy that promotes connectivity is advancing, there has been no systematic, evidence-based study that assesses whether connectivity conservation plans (CCPs) resulted in conservation outcomes, and identifies specific plan attributes that may favor successful implementation. To fill this gap, we gathered 263 terrestrial CCPs from around the world, characterized attributes of 109 plans by surveying plan authors, and conducted semi-structured interviews with authors and implementers of 77 CCPs. The production of CCPs started around 1990 and has increased markedly in all parts of the world, most notably in the United States (led by NGOs and a few states, with little federal involvement), Europe (led by the EU and national policies and implemented at local levels), and the Republic of South Africa (where national legislation mandates each municipality to map corridors and zone all land by 2020). All of the 109 plans that we examined in detail were followed by implementation actions such as crossing structures, ecological restoration, land purchases or easements, recognition of corridors through zoning or government designation, and public engagement. Interviewees emphasized the importance of initial buy-in from key government stakeholders, stakeholder involvement beyond initial buy-in, minimizing staff turnover, and transparent and repeatable procedures. Our quantitative and qualitative analyses similarly suggested that implementation of a CCP was enhanced by enduring partnerships among stakeholders, continuity of leadership, specific recommendations in the CCP using tools appropriately selected from a large toolbox, the existence of enabling legislation and policy, a transparent and repeatable scientific approach, adequate funding, and public outreach.